The State Role in the Economy - Manov, Vassil (Research Papers, 2009)
In the given situation a scientific analysis is made regarding one of the everlasting questions, connected (tangible or intangible) to every economic discussion. Unfortunately, this issue and the discussion of its address are burdened with too much ideology. These discussions do not concern the scientific analysis and the scientific reasoning. And the place, where this analysis is replaced with ideological cliches, inevitably leads to a mummification of the view of the economy and its demands for the tools that guarantee its operation and especially the tools that guarantee its development.Consciously or not, the adversaries of the state interference in the economy understand it as a constant in time. Their ideological argumentation doesn’t do anything but to leave the thesis that economy at the beginning of the twenty first century is the same as it was during Adam Smit’s time. The truth is that the anatomy and physiology of nowadays’ economy are radically different compared to the economy of the period of the industrial revolution.The people that accept the state interference in the economy are far from historical evidence too. And they are so because their ideas are also ideologically “substantiated”. Although it coincides with a growing objective need when the argumentation is not scientific it does not truly contribute to the materialization of this necessity.The ideological protection of both beliefs – for and against – state interference in economy equally get is the way of the good usage of the objective tendency of growing state role in the economy.